A wet dismantling process for the recycling of computer printed circuit boards - Pinho, Sílvia; Ferreira, Marco; Almeida, Manuel F. (Resources, conservation and recycling, 2018)
•A new process for dismantling the components on printed circuit boards was studied.•Process was assessed by visual analysis of components degradation.•Process was assessed by solutions characterization.•Recovery of aluminium and tin in WPCBs was achieved. In this research a new process for dismantling the components of the waste printed circuit boards (WPCBs) was developed. This process uses water and aqueous solutions of sodium hydroxide at conditions above solder melting temperatures which not only prevents pollution problems, but also separates the multilayers of WPCBs. The results show that removal of components in the WPCBs was achieved at 280 °C for 15 min with a 1 M NaOH solution. At these conditions glass fiber, epoxy resin and copper layers were separated and the resultant solution showed low concentration of copper, zinc, lead and iron ranging from 23 to 43 mg/kg of WPCBs and high concentration of tin and aluminium of 8 g/kg and 61 g/kg of WPCBs, respectively. About 97% of tin and 99% of aluminium in this solution were removed by precipitation.